Experimental Study on Double-Pass Solar Air Heater with and without using Phase Change Material (Journal of Engineering, 2019)
In this paper, an experimental study was conducted to enhance the thermal performance of a double-pass solar air heater (SAH) using phase change material (PCM) for thermal storage at climatic conditions of Baghdad city - Iraq. The double-pass solar air heater integrated with thermal storage system was manufactured and tested to ensure that the air heating reserved after the absence of the sun. The rectangular cavity filled with paraffin wax was used as a latent heat storage and incorporated into the lower channel of solar air heater. Experiments were carried out to evaluate the charging and discharging characteristics of two similar designed solar air collectors with and without using phase change material at a constant air mass flow rate of (0.0375 kg/sec). The parameters that affect the thermal performance of the SAH with and without the PCMs presented by solar radiation, the difference in air temperature, outlet air temperature, instantaneous thermal efficiency, and daily efficiency are evaluated. The experimental results show that when using the PCM, the temperature of the outlet air was enhanced and increased over the ambient temperature by (1.5 - 6.5 C) after sunset for 5 hours period. It was found that the instantaneous thermal efficiency of the heater using thermal storage exceeds 100% after sunset, this is due to a large amount of heat stored in the paraffin wax that has been released during the discharge process. Also, it was found that the daily efficiency of the double pass SAH integrated with and without thermal energy storage unit was (56, 47%) respectively.